Evaluasi Ergonomi Proses Rebus Garam dan Rekomendasi Intervensi di Laboratorium Industri Garam - Tabuni, Nuas; Kunhadi, Dedy; Fais, Moh Ainul; Sutejo, Bambang; Sakti, Yuni Krida (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The salt boiling process in small-scale industries is still largely performed manually, requiring repetitive physical activities that can potentially lead to musculoskeletal disorders among workers. This study aims to evaluate ergonomic risks in the salt boiling process and formulate improvement interventions to reduce these risks. A quantitative approach was applied through work posture observation, the Nordic Body Map (NBM) questionnaire, and posture assessment using the Rapid Entire Body Assessment (REBA) method on three operators in a salt industry laboratory. NBM results indicated that the highest complaints occurred in the back, waist, shoulders, and lower limbs. REBA analysis identified the drying stage as the most high-risk activity (score 10, very high), followed by salt cooking (score 8, high), and fire stove preparation (score 6, medium). Based on these findings, interventions such as adjusting worktable height, using lifting aids, and implementing job rotation are recommended to reduce injury risk while improving operator productivity.